TINJAUAN FIQIH MUAMALAH TERHADAP LOMBA BERBAYAR (HTM): ANALISIS UNSUR MAISIR DAN AKAD - Destia Vani; Rindu Permatasari; Fatmah Taufik Hidayat (Jurnal Riset Multidisiplin Edukasi, 2026)
Paid competitions or Entrance Ticket Prices (ETP) are an increasingly common phenomenon in modern society, ranging from talent contests, sports competitions, beauty contests, to academic competitions. In practice, organizers charge a registration fee from participants, and from these funds, part or all of it is turned into a prize for the winner. This study aims to analyze the legality of paid competitions from the perspective of Islamic commercial jurisprudence (fiqh muamalah), particularly concerning the element of maisir (gambling) and the validity of the contracts formed. The method used is library research with a normative approach based on the Quran, hadith, and scholars' opinions. The analysis shows that paid competitions can be categorized as halal or haram depending on the structure of the contract and the distribution of funds. If the ETP funds are turned into prizes without any third party bearing the cost and all participants contribute to a prize enjoyed by only some, then there is an element of maisir. On the other hand, if the prize comes from the organizer or an independent sponsor and the ticket price is only an administrative fee, then it is permissible.